Experience, Learning, & Consciousness: Advancing a Feminist-Materialist Theory of Adult Learning - Sara Carpenter (Adult Education Research Conference, 2009)
This paper theorizes from the literature of feminism, sociology, historical materialism, and adult education to advance a feminist-materialist approach to the long-standing debates regarding individual and social dimensions of learning and the relationships between experience, learning, and consciousness.